From Tweet to Conflict: Critical Discourse Analysis on Daryl Morey's Tweet about Hong Kong Protest - Sujiwa, Krisna; Munandar, Aris (Pengkajian Amerika, Universitas Gadjah Mada, 2024)
The research focuses on the hidden reason that made Daryl Morey's tweet controversial in America and China. This research uses a descriptive qualitative method. The primary data are response tweets of Daryl Morey's tweet about the Hong Kong protest and Daryl Morey's initial tweet about the Hong Kong protest. This research also applies a transnational perspective; Fairclough's three-dimensional CDA is used to analyze and answer two research questions: how Morey's tweet about Hong Kong became a political issue between the NBA and China and how this issue affected the NBA. The research finding shows five reasons on how Morey's controversy became a political issue between the NBA and China: There are differences in interpretations of the tweet; where the U.S. interpreted it as freedom of speech and expression, but the Chinese interpreted it as a challenge to their sovereignty. Basketball's popularity in China expanded the escalation of the conflict. Moreover, by using Transnational as perspective and CDA as theory, researcher able to demonstrate how a single tweet can incite a global uproar and become the catalyst for a costly conflict between two superpower nations.